VALIDITAS PERANGKAT PEMBELAJARAN BERORIENTASI POE (PREDICT-OBSERVE-EXPLAIN) PADA MATERI EKOLOGI DAN KEANEKARAGAMAN HAYATI KELAS VII - Mentari, Mentari; Nusantari, Elya; Hamidun, Marini Susanti; Husain, Ilyas H; Usman, Nurul Fajryani; Dama, Lilan (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Educators continue to encounter challenges in designing effective instructional tools, particularly in selecting learning models that actively engage students. This study aims to develop Predict-Observe-Explain (POE)-oriented learning tools for ecology and biodiversity topics that meet validity standards. The research employs the ADDIE development model—comprising Analysis, Design, Development, Implementation, and Evaluation phases. Validity assessments conducted by two expert validators resulted in scores of 93.75% for the Lesson Plan (RPP) and 87.5% for the Student Worksheet (LKPD), both classified as